W. W. Winnie Jr. Latin American Development : Theoretical, Sectoral and Operational Approaches. Latin American Studies, v. 8, Los Angeles, California, Latin American Center of California, UCLA, 1967, 255 p. - Villa Aguilera, Manuel (El Colegio de México A.C., 1971)
W. W. WINNIE, JR., Latin American Development : Theoretical, Sectoral and Operational Approaches. Latin American Studies, Vol. 8, Los Ángeles, California, Latin American Center of California, UCLA, 1967.